The leaching of trifloxysulfuron-sodium and pyrithiobac-sodium in soil columns as a function of soil liming - doi: 10.4025/actasciagron.v35i2.16349 - Naiara Guerra; Rubem Silvério de Oliveira Júnior; Jamil Constantin; Antonio Mendes de Oliveira Neto; Hugo de Almeida Dan; Guilherme Braga Pereira Braz (Acta Scientiarum. Agronomy, 2012)
Scarce research has been published concerning the effect of soil pH on the leaching potential of herbicides in tropical soils. Thus, we designed this study to evaluate the influence of soil liming on the leaching of trifloxysulfuron-sodium and pyrithiobac-sodium after simulated rainfall depths in soil columns. In the study, two trials were conducted simultaneously; the first experiment evaluated trifloxysulfuron-sodium (7.5 g ha-1), while the second experiment evaluated pyrithiobac-sodium (70 g ha-1). Both experiments were conducted in a randomized block design with a 2 x 4 x 5 factorial scheme and four replications. The design’s factors corresponded to 2 soil liming conditions (with or without liming), 4 simulated rainfall depths (0, 15, 30, and 45 mm) and 5 depths in the soil column (0-5, 5-10, 10-15, 15-20, and 20-25 cm). The trials were repeated, and only the source for the soil neutralization was changed, i.e., dolomitic limestone in Experiment 1 and calcium oxide in Experiment 2. Compared to trifloxysulfuron-sodium, the herbicide pyrithiobac-sodium indicated a greater potential for leaching. With more acidic soils, the leaching potential in limed soils was greater for both herbicides. Only the liming that used calcium oxide provided a significant leaching of trifloxysulfuron-sodium for depths greater than 20 cm. Simulated rainfall ≥ 15 mm provided leaching of pyrithiobac-sodium to a depth of 25 cm at near-neutral soil pH values.